PENINGKATAN SIKAP PERCAYA DIRI SISWA MELALUI MODEL TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA KARTU KELAS IV SD 2 BAKALAN KRAPYAK - Ulum, Ahmad Syaikhul; Sumarwiyah, Sumarwiyah; Pratiwi, Ika Ari (Universitas Muria Kudus, 2019)
This research aims to measure the improvement of students’ confidence and improvement of teacher’ teaching skills the fourth grade students at SD 2 Bakalan Krapyak.This classroom action research was carried out in two cycles.The result of this research shown there are significant improvement of Students'confidence in learning realmof attitude at the pre-cycle level was 46% as a not good category, after doing the research in the cycle I it changed into 69% as a good enough category and increased more in thecycle IIto be 84% as a good category. The management of Teams Games Tournament model learning also increased in cycle I 77% as a good category to 87% as a good category in cycle II. It proves that used of Teams Games Tournament model use cards media can improve attitude self confidence in fourth grade students theme 4 at SD 2 Bakalan Krapyak.